2001
DOI: 10.1183/09031936.01.00268401
|View full text |Cite
|
Sign up to set email alerts
|

Infection: friend or foe in the development of atopy and asthma?

Abstract: There is increasing evidence from epidemiological studies to support the "hygiene hypothesis" with regard to the development of allergic diseases. This review will discuss the epidemiological findings relating to atopy and asthma, separately.The strongest arguments in favour of the "hygiene hypothesis" are the findings relating early life day care attendance to a significantly reduced risk of atopy and asthma, and the strong link between sibship size and the occurrence of atopy as confirmed by numerous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1
5

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 90 publications
(97 reference statements)
2
44
1
5
Order By: Relevance
“…The factors in farming families that could explain the protective effect against atopy might include, as stated earlier (36), larger family size, frequent heating with wood, more pets, less maternal smoking, more dampness and different dietary habits. However, none of these factors have been shown to explain the differences to any major extent.…”
Section: Exposure To Farm/country Environment and Petsmentioning
confidence: 88%
See 1 more Smart Citation
“…The factors in farming families that could explain the protective effect against atopy might include, as stated earlier (36), larger family size, frequent heating with wood, more pets, less maternal smoking, more dampness and different dietary habits. However, none of these factors have been shown to explain the differences to any major extent.…”
Section: Exposure To Farm/country Environment and Petsmentioning
confidence: 88%
“…However, none of these factors have been shown to explain the differences to any major extent. By contrast, contact to livestock and poultry has been found to explain much of the inverse association between farm environment and atopy (36,115,116). These data suggest that exposure to a wide spectrum of microorganisms and bacterial products, such as LPS, may be responsible for the lower prevalence of atopic diseases among individuals grown up on a farm or rural area.…”
Section: Exposure To Farm/country Environment and Petsmentioning
confidence: 94%
“…Since CD8 ϩ T cell responses to the immunogen were demonstrated in several of these settings, it is plausible that CD8 ϩ T cells were involved in the down-regulation of Th2 activities. This suggested mechanism might be relevant to the "hygiene hypothesis" which proposes that the current rise in the incidence of allergic diseases is related to decreased exposure to certain pathogens in early life (52). On the basis of our findings, we suggest that infectious or pharmacological agents promoting CD8 ϩ T cell activities in early life might indeed reduce the risk of developing Th2 sensitization and associated atopic disorders.…”
Section: Discussionmentioning
confidence: 72%
“…In a very large Finnish study, which included half a million subjects aged 14 months to 19 years, Paunio et al (2000) reported that measles and atopy had occurred more frequently together than expected. Furthermore Bager et al (2002) reported that Danish women with measles during the first year of life was associated with a 3.4 fold increase in the odds ratio of atopy compared to women without measles before the age of 7 years, while other investigations revealed that either measles had a protective effect against atopic disorders or there was no relationship between them (Farooqi and Hopkin 1998;von Mutius 2001). The controversy about this issue may be explained by biphasic response of natural measles infection; in the early phase T-helper (Th)-1 type immune response with increased levels of interleukin (IL)-12 is a characteristic feature, while in the later phase a prolonged Th-2 type response with increased levels of IL-4 and Ig-E predominates which subsequently favors the development of atopic conditions (von Hertzen and Haahtela 2004).…”
Section: Discussionmentioning
confidence: 99%